Pengembangan Pertanian Tebu Di Kabupaten Sleman Dan Dampaknya Terhadap Kondisi Sosial – Ekonomi Petani: Studi Pada Koperasi Tebu Sido Makmur - Ilma Fatimah Yusuf (Universitas Islam Kadiri, 2022)
Sleman Regency is a productive area, its agriculture is known to support food security. This is proven by the various awards given by the Minister of Agriculture, one of which is a member of the Sido Makmur sugar cane farmer cooperative, which is located in Kalasan District, Sleman Regency. The award that can be obtained is, of course, due to the development of sugarcane farming. So, the purpose of this research is to examine the development of sugarcane farming and its impact on socio-economic conditions, which is focused on the Sido Makmur Cooperative. The method in this study uses descriptive analysis, with purposive sampling technique. While the data collection techniques were carried out by means of observation, interviews and documentation. The data analysis uses data reduction techniques, categorization, data display and drawing conclusions. The results of the study show several things. The first, sugarcane farmers who are members of the Sido Makmur Cooperative have a maximum education up to high school level. Second, the land cultivated by sugarcane farmers is varied, at least 1.5 Ha, while at most 10 Ha. There is land that is cultivated on a lease basis, but there is also one that is owned by yourself. Third, cooperatives have a role in the development of sugarcane agriculture through the steps of forming a business unit for the procurement of retail fertilizer sales, rental of agricultural production equipment, savings and loans and building relationships with sugar factories. Fourth, the role of the cooperative can encourage members of sugarcane farmers to remain productive and as an effort to improve the welfare of members.